Intradural Extramedullary Epidermoid Cyst at the Conus Medullaris level with Thoracic Syringomyelia: a Case Report - Akgun, Bekir; Ergun, Ahmet Cemil; Ozercan, Ibrahim Hanifi; Kok, Selman (Charles University Faculty of Medicine in Hradec Kralove, 2019)
Spinal epidermoid cysts are benign tumors. Syringomyelia secondary to intramedullary tumors are frequently observed. However, the association between syringomyelia and spinal intradural extramedullary epidermoid cyst in the conus medullaris region is extremely rare. We present the case of a 3-year-old male who was admitted with paraparesis and urinary retention. Magnetic resonance imaging (MRI) of the spine demonstrated intradural extramedullary lesion, compatible with epidermoid cyst, that at the conus medullaris level and a large syringomyelia extending from T4 to L1 vertebrae. Total microsurgical excision of the cyst was performed. No additional drainage was carried out for the syringomyelic cavity. Histopathological examination verified the diagnosis of the epidermoid cyst. Total excision of the cyst and disappearance of the syringomyelia were observed on MRI at 15 days postoperatively. We have clarified the etiology, clinical, histopathological and radiological features, differential diagnosis, and treatment modalities of spinal epidermoid cysts. In addition, we have discussed the possible mechanisms of syringomyelia formation in spinal intradural lesions. © 2019 The Authors.
Keywords: conus medullaris; epidermoid cyst; spine; syringomyelia